ANALISIS EFEKTIVITAS SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL PERKREDITAN PADA PT. BANK PEMBANGUNAN DAERAH PAPUA CABANG MANADO - Krar, Sonaria; Tinangon, Jantje J.; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Â AÂ  goodÂ  AccountingÂ Â  InformationÂ Â  SystemÂ  canÂ  help Â companyÂ  toÂ  provideÂ  theÂ  companyâsÂ  needÂ  forÂ Â  otherÂ  informationÂ  relatedÂ Â  toÂ  busynessÂ  processÂ  thatÂ  existÂ  withinÂ  theÂ  company. ThisÂ  researchÂ  studyÂ  atÂ  PT. RegionalÂ  bankÂ  developmentÂ  papuaÂ  branchÂ  manado.ThisÂ  studyÂ Â  aimsÂ  toÂ Â  knowÂ  effectivenessÂ  ofÂ Â Â  information accountingÂ  systemÂ  andÂ  internalÂ  controlÂ  ofÂ  kreditÂ  onÂ  PT.regionalÂ Â  bankÂ  developmentÂ  papuaÂ  branchÂ  manado.ThisÂ  studyÂ  used a deskriptiveÂ  qualitativeÂ  methodÂ  isÂ  aÂ  methodÂ  thatÂ  isÂ  doneÂ  byÂ  classifyingÂ  dataÂ  and Â Â inormationÂ  whichÂ  isÂ  obtainedÂ  byÂ  variousÂ  technicquesÂ  suchÂ  asÂ  survey, interviews,Â  andÂ  others. SoÂ  getÂ  aÂ  relevantÂ  conclusion.The resultsÂ  ofÂ Â  theÂ Â  analysisÂ Â  ofÂ  theÂ  conclusionÂ  thatÂ  theÂ  informationÂ  systemÂ Â  andÂ Â  internalÂ  controlÂ  ofÂ  PT. bankÂ  PapuaÂ  manadoÂ  branchÂ  hasÂ  beenÂ Â  runningÂ  well, andÂ  inÂ  accordanceÂ  withÂ  proceduresÂ  thatÂ  haveÂ  beenÂ  setÂ  byÂ  theÂ  bankÂ  indonesian.Â  AllreadyÂ  meetÂ  theÂ  characteristicsÂ  andÂ Â  elementsÂ Â  ofÂ Â  internalÂ  control.Keywords : InformationÂ  AccountingÂ  System,Â  InternalÂ  control,Â  Credit.